How national employment systems relate to employee involvement: A decomposition analysis of Germany, the UK and Sweden - Kirchner, Stefan; Hauff, Sven (Socio-Economic Review, 2019)
We investigate general claims that national institutional conditions relate to employee involvement across countries. Using a decomposition analysis, we examine how much of the key domains of national employment systems contribute to differences in employee involvement in Germany, the UK and Sweden. Drawing on the 2015 European Working Conditions Survey (EWCS), our decomposition analysis explains between 40% and 65% of the cross-national differences. These differences stem from key national employment systems domains, namely the management system, information and communication technology use, as well as training and education. We show that these domains contribute simultaneously and with different weights to cross-national differences, and conclude that domains' contributions reflect the specific institutional characteristics of the investigated national employment systems.
CRIS-Team Scopus Importer:2025-04-09
Keywords: D02 production and organizations; Germany; J81 working conditions; labor market institutions; P52 comparative studies of particular economies; personnel management; political economy; Sweden; United Kingdom; work